Comparative oncological outcomes after radical prostatectomy or external beam radiation therapy plus androgen deprivation therapy in men with clinical T3b prostate cancer. (8th February 2022) - Lee, Wonchul; Lim, Bumjin; Kyung, Yoon Soo; Kim, Choung‐Soo
Abstract : Objective: To compare oncological outcomes in men with clinical T3b prostate cancer who underwent radical prostatectomy or a combination of radiation therapy plus androgen deprivation therapy. Methods: Men with clinical T3b prostate cancer who underwent radical prostatectomy or radiation therapy plus androgen deprivation therapy between 2007 and 2014 were evaluated. All patients were relatively healthy, with Eastern Cooperative Oncology Group performance status of 0 or 1 without nodal or distant metastasis. Cancer‐specific survival was analyzed. Age, Charlson Comorbidity Index, biopsy Gleason score and pretreatment prostate‐specific antigen were adjusted by propensity score matching. The Cox proportional hazards model was used to assess factors prognostic of cancer‐specific survival. Results: Of the 152 patients with clinical T3b prostate cancer, 45 underwent radical prostatectomy, and 107 underwent radiation therapy plus androgen deprivation therapy between 2007 and 2014. The mean cancer‐specific survival was significantly longer in the radical prostatectomy than in the radiation therapy plus androgen deprivation therapy group ( P = 0.029). Age, Charlson Comorbidity Index and pretreatment prostate‐specific antigen were significantly higher in the radiation therapy plus androgen deprivation therapy group. In the propensity score matched population of 24 patients each, the median cancer‐specific survival remained significantly longer in the radical prostatectomy than in the radiation therapy plus androgen deprivation therapy group (not reached vs 112.93 ± 11.94 months, P = 0.026). Multivariate analysis showed that undergoing radiation therapy plus androgen deprivation therapy was the only significant poor prognostic factor for cancer‐specific survival (hazard ratio 6.694, 95% confidence interval 1.642–27.592, P = 0.008). Conclusion: Cancer‐specific survival was significantly longer in men with clinical T3b prostate cancer who underwent radical prostatectomy than radiation therapy plus androgen deprivation therapy, suggesting that radical prostatectomy can be a better treatment option for the initial definitive treatment for these patients.